2015
DOI: 10.1007/s13213-015-1124-z
|View full text |Cite
|
Sign up to set email alerts
|

Tanticharoenia aidae sp. nov., for acetic acid bacteria isolated in Vietnam

Abstract: Tanticharoenia aidae sp. nov. was introduced for two strains, designated as VTH-Ai06 T and VTH-Ai07, which were isolated from the stems of sugar cane collected in Vietnam. In a phylogenetic tree based on 16S rRNA gene sequences derived from the neighbor-joining method, the two strains formed a cluster along with the type strain of Tanticharoenia sakaeratensis with a bootstrap value of 64 %. The pair-wise 16S rRNA gene sequence similarity was 98.3 % between strain VTH-Ai06 T and the type strain of T. sakaeraten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This group of bacteria is characterized by the common ability to catabolize sugars and produce acidic compounds from them (e.g., acetic acid). Specifically, Tanticharoenia produces acid from ethanol and multiple sugars, and can grow in the presence of 0.35% acetic acid [69].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This group of bacteria is characterized by the common ability to catabolize sugars and produce acidic compounds from them (e.g., acetic acid). Specifically, Tanticharoenia produces acid from ethanol and multiple sugars, and can grow in the presence of 0.35% acetic acid [69].…”
Section: Discussionmentioning
confidence: 99%
“…This group of bacteria is characterized by the common ability to catabolize sugars and produce acidic compounds from them (e.g., acetic acid). Specifically, Tanticharoenia produces acid from ethanol and multiple sugars, and can grow in the presence of 0.35% acetic acid [69]. Interestingly, Asaia is the only Acetobacteraceae that does not produce acetic acid from ethanol but can oxidize acetate and lactate to carbon dioxide [70].…”
Section: Discussionmentioning
confidence: 99%
“…Most representatives of this group, Gluconacetobacter , Acetobacter , Komagataeibacter , Swaminathania , Asaia , Nguyenibacter and Tanticharoenia are commonly associated with the rhizosphere of several plants and also occupy inside roots, leaves and other plant tissues as endophytes ( Cavalcante & Döbereiner 1988 ; Reis & Teixeira 2015 ; Vu et al . 2013 ; 2016 ). In vitro inhibition of fungal phytopathogens on PDA media against F. moniliforme showed that all 14 isolates exhibited PIRG values at variable levels ranging from 16.73% to 49% in comparison to control.…”
Section: Discussionmentioning
confidence: 99%
“…1989 ). Tanticharoenia aidae and Acetobacter sacchari , were the second and third species, respectively, of plant growth promoting bacteria associated with sugarcane ( Vu et al . 2016 ; 2019b ).…”
Section: Introductionmentioning
confidence: 99%
“…Gram staining was carried out using Gram-stain kit (Sigma) according to the manufacturer's instructions. Motility was *Data from: a, Nishijima et al [46]; b, Franke et al [47]; c, Gillis et al [20]; d, Gossele et al [48]; e, Tazato et al [49]; f, Fuentes-Ramírez et al [50]; g, Lisdiyanti et al [51]; h, Yukphan et al [53]; i, Vu et al [54]; j, Vu et al [55]; k, Urakami et al [52]. †The data were inferred from genome sequences.…”
mentioning
confidence: 99%